SCHOLARSHIP AND ACTIVISM TOWARD VIOLENCE AGAINST WOMEN - Nur Hasyim (Teosofia: Indonesian Journal of Islamic Mysticism, 2017)
This paper discusses on the relationship between scholarship and activism and argues that one is an integral part of another. Scholarship provides an analytical framework and guidance for activism in understanding the social injustice and oppression. It also help activism to develop strategies to address the problem. At the same time, activism provides a valid evidence and data from which theories are generated. Based on the author study on the movement to end violence against women, this paper indicates two types of relationship between scholarship and activism; first, direct connection in which the paper presents some examples of activismagainst violence against women in the world that are carried out by scholars. Second, indirect connection where the paper presents some scholarly works that are influential for anti-violence against women activism.